The Life Intense: A Modern Obsession - Garcia, Tristan 1981-; RayAlexander, Abigail; RayAlexander, Christopher 1983-; Cogburn, Jon (Edingburgh Edinburgh University Press Ltd, 2018)
"Our lives today are oppressed by the demand that we live, feel and experience with ever greater intensity. We are enticed to try exotic flavours and smells; urged to enjoy a wide range of sexual experiences; pushed to engage in extreme sports and recreational drugs - all in the pursuit of some new, unheard-of intensity. Tristan Garcia argues that such intensity rarely lives up to its promise. It always comes at a price: one that defines the ethical predicament of contemporary life. The notion of intensity was the hidden key to Garcia's landmark book Form and Object. In The Life Intense, the first part of his ambitious Letting Be trilogy, he begins to develop it in detail. This first book focuses on ethics; the forthcoming two books look at politics and metaphysics respectively."--Publisher's description.
1. An Image -- 2. An Idea -- 3. A Concept -- 4. A Moral Ideal -- 5. An Ethical Ideal -- 6. An Opposing Concept -- 7. An Opposing Idea -- 8. An Opposing Image.
Includes bibliographical references ( [pages [149]-156) and index.
Keywords: Ethics